Affect Disposition(ing): A Genealogical Approach to the Organization and Regulation of Emotions - Bösel, Bernd (2018)
The “affective turn” has been primarily concerned not with what affect is, but what it does. This article focuses on yet another shift towards how affect gets organized, i.e., how it is produced, classified, and controlled. It proposes a genealogical as well as a critical approach to the organization of affect and distinguishes between several “affect disposition(ing) regimes”—meaning paradigms of how to interpret and manage affects, for e.g., encoding them as byproducts of demonic possession, judging them in reference to a moralistic framework, or subsuming them under an industrial regime. Bernard Stiegler’s concept of psychopower will be engaged at one point and expanded to include social media and affective technologies, especially Affective Computing. Finally, the industrialization and cybernetization of affect will be contrasted with poststructuralist interpretations of affects as events.